Analysis Of Business Development Strategy In The Metaverse Industry Through The Business Model Canvas (BMC) And SWOT Analysis Approach At WIR Group - Hengki Vieri Panogari Vincentius Simarmata; Azizah Fauziyah; Ismail Yusup (SEAN Institute, 2024)
In this decade, technology and science have developed rapidly, creating a new phenomenon known as the metaverse. The metaverse is a concept of a virtual world that combines physical and digital realities, presenting a virtual civilization that provides users the opportunity to explore, communicate, collaborate, and participate in various activities digitally. This study aims to analyze the business development strategy at WIR Group. The research uses a qualitative approach with the Business Model Canvas (BMC) and SWOT analysis. The object of this research is WIR Group or PT WIR Asia Tbk., a company operating in the metaverse field. The findings reveal weaknesses in customer segments, channels, customer relationships, and key partnerships in the Business Model Canvas (BMC) of WIR Group, which require improvements and strategic implementation. The SWOT analysis results show that the company has prominent internal factors (strengths and opportunities) but needs to anticipate external factors (weaknesses and threats) to enhance its market share. Therefore, based on these findings, several strategies can be adopted, including strengthening business expansion plans, conducting both direct and indirect marketing approaches, contributing to the empowerment of the smart society, prioritizing customer satisfaction and comfort, innovating, etc.